Pre-school Teachers' Informatics and Information Literacy - Tatković, Nevenka; Ružić, Maja; Pečarić, Đilda (2006)
The life and activities of every man in the period of transition from the second into the third millennium have been marked by epochal changes which appear as the consequence of scientific and technological revolution dominated by highly developed information and communication technology. Informatics and information education based on information and communication technologies is information society’ s basic trait and premise for technological education of all persons involved in the educational process. The work deals with the necessity of transformation of the present pre-school teachers’ concept of informatics and information education subject to conditions of reformatory processes in higher education of the Republic of Croatia. Suggestions and possible solutions for the change of curriculum and pedagogical aspects of the realization of pre-school teachers’ education are provided.
Projekt MZOS
Projekt MZOS
ENG